ANALISIS KESALAHAN MEIREIKEI DAN IKOUKEI PADA MAHASISWA ANGKATAN 2009 PROGRAM STUDI SASTRA JEPANG UNIVERSITAS BRAWIJAYA - BAKHSIN, MUTHIA HULWUN (Jurnal Ilmiah Mahasiswa FIB, 2013)
Language is used as verbal communication in a community to work together, interact, and yourself identify. If the speaker uses the wrong word formation or not appropriate, the other person will be confused in digesting the meaning of our words. In Japanese language, there are changes in verb form. For example is Japanese command and call form verb (meireikei and ikoukei) changing. Therefore, the title of this study is ‘Error Analysis of Japanese command and call form sentences of   Japanese Literature student class of 2009 Brawijaya University’. There are two problems to be solved in this study, namely : (1) What kind of mistakes do students of Japanese Literature class of 2009 Brawijaya University in using form of the command and call in Japanese sentences ? (2) What causes the error of Japanese Literature student class of 2009 Brawijaya University in using the command and call form in Japanese sentences? This study uses qualitative descriptive type and used questioner as data sources. The respondents are Japanese Literature student class of 2009 Brawijaya University. In the questioner, there are 20 question of command and call form of Japanese sentences. Based on the result of the study, in reality there are many students which choosed the wrong answer when did the questioner. In changing Japanese command and call form, there are students who did not remember about that. Beside that, there are students who  did not choosed the answer thoroughly. It is the cause of error what the students did.   Key words : Error analysis, Meireikei, Ikoukei.